Test-retest reliability of the ‘Reading the Mind in the Eyes’ test: a one-year follow-up study - Fernández-Abascal, Enrique G (BioMed Central, 2013)
BACKGROUND: The ‘Reading the Mind in the Eyes’ (Eyes) test is an advanced test of theory of mind. It is widely used to assess individual differences in social cognition and emotion recognition across different groups and cultures. The present study examined distributions of responses and scores on a Spanish version of the test in a non-clinical Spanish adult population, and assessed test-retest reliability over a 1-year interval. METHODS: A total of 358 undergraduates of both sexes, age 18 to 65 years, completed the Spanish version of the test twice over an interval of 1 year. The Bland-Altman method was used to calculate test-retest reliability. RESULTS: Distributions of responses and scores were optimal. Test-retest reliability for total score on the Eyes test was .63 (P <.01), based on the intraclass correlation coefficient. Test-retest reliability using the Bland-Altman method was fairly good. CONCLUSIONS: This is the first study providing evidence that the Eyes test is reliable and stable over a 1-year period, in a non-clinical sample of adults.